2015
DOI: 10.1371/journal.pone.0130993
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anti-Dementia and Nootropic Treatments on the Mortality of Patients with Dementia: A Population-Based Cohort Study in Taiwan

Abstract: BackgroundFew studies have examined the contribution of treatment on the mortality of dementia based on a population-based study.ObjectiveTo investigate the effects of anti-dementia and nootropic treatments on the mortality of dementia using a population-based cohort study.Methods12,193 incident dementia patients were found from 2000 to 2010. Their data were compared with 12,193 age- and sex-matched non-dementia controls that were randomly selected from the same database. Dementia was classified into vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
(49 reference statements)
1
23
1
Order By: Relevance
“…The effect of antidementia drugs on survival in people without Down syndrome is uncertain; some studies report increased survival in people prescribed antidementia drugs, 21 , 22 yet other studies do not 23 24 A underlying mechanism by which antidementia medications might reduce mortality has not been established but it has been hypothesised that the effect is mediated by protective effects of the drugs on atherosclerotic cardiovascular risk 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antidementia drugs on survival in people without Down syndrome is uncertain; some studies report increased survival in people prescribed antidementia drugs, 21 , 22 yet other studies do not 23 24 A underlying mechanism by which antidementia medications might reduce mortality has not been established but it has been hypothesised that the effect is mediated by protective effects of the drugs on atherosclerotic cardiovascular risk 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The NHI program was launched in 1995 to provide health care to all residents, and currently services more than 23 million people, representing approximately 99% of Taiwan’s population. The NHI database contains registration files and original claims data for care reimbursements for all enrollees, making it one of the world’s largest and most complete nation-wide, population-based health care services datasets [ 17 , 18 ]. In this dataset, the diagnostic codes are formatted according to the International Classification of Diseases , Ninth Revision , Clinical Modification (ICD-9-CM) .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported associations between antidementia drug use and reduced mortality in the community [18] , [21] , [22] , [23] , [39] , [40] . There is no previous reporting on associations between antidementia treatment and mortality after admission in this high-risk population of in-patients.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent systematic review and meta‐analysis of randomized placebo‐controlled clinical trials, the use of AChEIs was associated with reduced mortality [20], and the authors suggest this finding may indicate some disease‐modifying effect of these drugs. This finding however is not consistent across all studies: some studies show a reduction in mortality in people who were prescribed antidementia medication [18,21–23], one study shows a reduction in cardiovascular deaths [24], and another has failed to find an association [15].…”
Section: Introductionmentioning
confidence: 93%